Early Diagnosis of Mycoplasma pneumoniae in Children: Simultaneous Amplification and Testing (SAT) Is the Key - Li, Jieqiong; Sun, Lin; Wu, Xirong; Guo, Yan; Jiao, Weiwei; Xiao, Jing; Xu, Baoping; Shen, Adong (Frontiers in Pediatrics, 2019)
Objective: The effective diagnosis of Mycoplasma pneumoniae (MP) pneumonia (MPP) in children has been hampered by the difficulty of achieving an early diagnosis. The simultaneous amplification and testing (SAT) has the potential for early diagnosis of MP in children. Methods: Of the 1,180 children enrolled in this study, 169 were MPP antibody (Ab) seroconversion positive, 641 showed MPP positivity with a single Ab test, and 370 were MPP negative. Sera and pharyngeal swabs were collected for antibody testing and SAT detection, respectively, on admission. When the samples were Ab negative, the paired -Ab test was requested for MP 7 days later. Results: Using the Ab results as the diagnostic standard, the sensitivity, specificity, positive predictive values (PPV), and negative predictive values (NPV) for SAT were 72.8, 95.1, 97.0, and 61.5%, respectively. SAT had superior diagnostic value in the MPP group who had undergone Ab seroconversion (sensitivity: 82.2%; NPV: 92.1%) and in the short-course group also (sensitivity: 81.0%; NPV: 81.3%). Good agreement was observed between SAT and the paired-Ab results (kappa value = 0.79; P < 0.001), but there was a lack of consistency between SAT and the single-Ab test results on admission (kappa value = 0.54, P < 0.001). Conclusions: SAT is a rapid, sensitive, and specific method for MP diagnosis in pediatric patients. Our results indicate its value as an effective diagnostic tool for detecting MPP at the initial stage of an infection.